The bigger the threat, the longer the gaze? A cross-cultural study of Somalis and Czechs - Štolhoferová, Iveta; Frynta, Daniel; Janovcová, Markéta; Rudolfová, Veronika; Elmi, Hassan Sh Abdirahman; Rexová, Kateřina; Berti, Daniel Alex; Král, David; Sommer, David; Landová, Eva; Frýdlová, Petra (Frontiers in Psychology, 2023)
High fear reaction, preferential attention, or fast detection are only a few of the specific responses which snakes evoke in humans. Previous research has shown that these responses are shared among several distinct cultures suggesting the evolutionary origin of the response. However, populations from sub-Saharan Africa have been largely missing in experimental research focused on this issue. In this paper, we focus on the effect of snake threat display on human spontaneous attention. We performed an eye-tracking experiment with participants from Somaliland and the Czechia and investigated whether human attention is swayed toward snakes in a threatening posture. Seventy-one Somalis and 71 Czechs were tested; the samples were matched for gender and comparable in age structure and education level. We also investigated the effect of snake morphotype as snakes differ in their threat display. We found that snakes in a threatening posture were indeed gazed upon more than snakes in a relaxed (non-threatening) posture. Further, we found a large effect of snake morphotype as this was especially prominent in cobras, less in vipers, and mostly non-significant in other morphotypes. Finally, despite highly different cultural and environmental backgrounds, the overall pattern of reaction towards snakes was similar in Somalis and Czechs supporting the evolutionary origin of the phenomenon. We concluded that human attention is preferentially directed toward snakes, especially cobras and vipers, in threatening postures.